Pengaruh Intellectual Capital Terhadap Profitabilitas, Produktivitas Dan Nilai Perusahaan (Studi Empiris pada Perusahaan Perbankan yang terdaftar di Bursa Efek Indonesia periode 2011- 2015) - Setya Rini, Ida; , Drs. Eko Sugiyanto, M.Si (2017)
This study was conducted to examine the effect of intellectual capital on profitability, productivity and value of the company. The population used in this study were banking companies listed in Indonesia Stock Exchange Year 2011-2015. The sampling technique used is purposive sampling technique in order to obtain a sample of 20 banking companies that have the criteria. The data used are annual data obtained from published financial statements of state-owned banks during the years 2011-2015. Data analysis technique used is multiple regression analysis with help of Eviews program. The results of this study indicate that the Model 1, simultaneously Intellectual capital variables affect the ROA, but partially independent variables were not significant effect on ROA is Vace. Model 2, simultaneously Intellectual capital affect the ROE, but partially independent variables were not significant effect on ROE is VAHC. Model 3, simultaneously Intellectual capital affects productivity, but partially of all independent variables had no significant effect on productivity. Model 4, simultaneously Intellectual capital affect the value of the company, but in pastial semuya independent variables was also no significant effect on the value of the company.